ROLE OF DETERMINING THE PRICE OF LAND EXTENSION FOR PUBLIC INTEREST PROVIDED BY APPRAISAL AND LAND OFFICE IN COMPLIANCE WITH JUSTICE ELEMENTS - Mila Verdiyani Larasati (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The role of appraisal and Land Office in determining prices in land acquisition for the purpose of public interest, basically land acquisition has same understanding as land acquisition. Regulations regarding land acquisition are also regulated in land acquisition, the formulation of the problem in this study is the determination of price for compensation for land used for public interest and legal settlement methods in case of a dispute if the price for compensation is not in accordance with the agreement. The research in this journal is normative empirical, the type of data used in this research is secondary data, the way data is obtained using secondary data through library techniques, the approach used in this research is constitutional approach and case approach, the analysis used in journal writing This is an inductive data analysis, the results of research in this journal are a method of determining the price of compensation for land which will be the object of land acquisition by looking at market value. it will take 14 days after receiving the pricing that has been given by the appraisal.